Clinical and cost-effectiveness of the Managing Agitation and Raising Quality of Life (MARQUE) intervention for agitation in people with dementia in care homes: a single-blind, cluster-randomised controlled trial. (April 2019) - Livingston, Gill; Barber, Julie; Marston, Louise; Stringer, Aisling; Panca, Monica; Hunter, Rachael; Cooper, Claudia; Laybourne, Anne; La Frenais, Francesca; Reeves, Suzanne; Manela, Monica; Lambe, Katie; et al.
Summary: Background: Many people with dementia living in care homes have distressing and costly agitation symptoms. Interventions should be efficacious, scalable, and feasible. Methods: We did a parallel-group, cluster-randomised controlled trial in 20 care homes across England. Care homes were eligible if they had 17 residents or more with dementia, agreed to mandatory training for all eligible staff and the implementation of plans, and more than 60% of eligible staff agreed to participate. Staff were eligible if they worked during the day providing face-to-face care for residents with dementia. Residents were eligible if they had a known dementia diagnosis or scored positive on screening with the Noticeable Problems Checklist. A statistician independent of the study randomised care homes (1:1) to the Managing Agitation and Raising Quality of Life (MARQUE) intervention or treatment as usual (TAU) using computer-generated randomisation in blocks of two, stratified by type of home (residential or nursing). Care home staff were not masked to the intervention but were asked not to inform assessors. Residents with dementia, family carers, outcome assessors, statisticians, and health economists were masked to allocation until the data were analysed. MARQUE is an evidence-based manualised intervention, delivered by supervised graduate psychologists to staff in six interactive sessions. The primary outcome was agitation score at 8 months, measured using the Cohen-Mansfield Agitation Inventory (CMAI). Analysis of the primary outcome was done in the modified intention-to-treat population, which included all randomly assigned residents for whom CMAI data was available at 8 months. Mortality was assessed in all randomly assigned residents. This study is registered with the ISRCTN registry, number ISRCTN96745365. Findings: Between June 14, 2016, and July 4, 2017, we randomised ten care homes (189 residents) to the MARQUE intervention and ten care homes (215 residents) to TAU. At 8 months, primary outcome data were available for 155 residents in the MARQUE group and 163 residents in the TAU group. At 8 months, no significant differences in mean CMAI scores were identified between the MARQUE and TAU groups (adjusted difference −0·40 [95% CI −3·89 to 3·09; p=0·8226]). In the intervention care homes, 84% of all eligible staff completed all sessions. The mean difference in cost between the MARQUE and TAU groups was £204 (−215 to 623; p=0·320) and mean difference in quality-adjusted life-years was 0·015 (95% CI −0·004 to 0·034; p=0·127). At 8 months, 27 (14%) of 189 residents in the MARQUE group and 41 (19%) of 215 residents in the TAU group had died. The prescription of antipsychotic drugs was not significantly different between the MARQUE group and the TAU group (odds ratio 0·66; 95% CI 0·26 to 1·69, p=0·3880). Interpretation: The MARQUE intervention was not efficacious for agitation although feasible and cost-effective in terms of quality of life. Addressing agitation in care homes might require resourcing for delivery by professional staff of a more intensive intervention, implementing social and activity times, and a longer time to implement change. Funding: UK Economic and Social Research Council and the National Institute of Health Research.